Pengaruh Lingkungan Kerja, Disiplin Kerja Dan Motivasi Terhadap Kinerja Karyawan Pada Kantor Camat Woha Kab. Bima - Unitaris, Rahmat; Basalamah, Muhammad Ridwan; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research is a type of quantitative research. Where the population in this study was used as a sample using a saturated sample with a population of 32 respondents. By collecting data using the questionnaire method, the aim is to determine the simultaneous and partial influence between the variables of the influence of work environment, discipline, work and motivation on employee performance. The work environment has a partially positive and significant influence on employee performance. Work Discipline has a partial influence on Employee Performance. Motivation has a partially positive and significant influence on Work Commitment. The results of the Coefficient of Determination concluded that the magnitude of the influence of the Work Environment, Work Discipline and Motivation variables on Employee Performance, with the remainder influenced by other variables not examined in this research Keywords: Work Environment, Work Discipline, and Motivation on Employee Performance